2012
DOI: 10.4049/jimmunol.1200955
|View full text |Cite
|
Sign up to set email alerts
|

Th17 Cells Upregulate Polymeric Ig Receptor and Intestinal IgA and Contribute to Intestinal Homeostasis

Abstract: Although enriched in normal intestines, the role of CD4+ Th17 cells in regulation of the host response to microbiota, and whether and how they contribute to intestinal homeostasis is still largely unknown. It is also unclear whether Th17 cells regulate intestinal IgA production, which is also abundant in the intestinal lumen and plays a crucial role as the first defense line in host response to microbiota. In this study, we found that intestinal polymeric Ig receptor (pIgR) and IgA production was impaired in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
189
1
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 207 publications
(205 citation statements)
references
References 45 publications
13
189
1
2
Order By: Relevance
“…Effective induction of IL-17 is desirable when designing a vaccine against H. pylori infection, since one of the functions of IL-17 is to recruit neutrophils, which have been shown to be essential in reducing the bacterial loads in the stomachs of vaccinated mice (28), although DeLyria et al have reported that in mice immunized with H. pylori lysate antigens and CT, neutrophils can be recruited to the stomach after challenge independent of IL-17A (29). However, IL-17 has multiple roles, and we believe that its main function in H. pylori infection is to promote bacterial clearance by possibly recruiting bactericidal neutrophils and also to stimulate local IgA antibody formation (30). We noted that vaccination with H. pylori antigens together with either dmLT or CT as an adjuvant was associated with enhanced inflammation in the stomach (postimmunization gastritis) after challenge with live bacteria.…”
Section: ⌬Ctmentioning
confidence: 89%
“…Effective induction of IL-17 is desirable when designing a vaccine against H. pylori infection, since one of the functions of IL-17 is to recruit neutrophils, which have been shown to be essential in reducing the bacterial loads in the stomachs of vaccinated mice (28), although DeLyria et al have reported that in mice immunized with H. pylori lysate antigens and CT, neutrophils can be recruited to the stomach after challenge independent of IL-17A (29). However, IL-17 has multiple roles, and we believe that its main function in H. pylori infection is to promote bacterial clearance by possibly recruiting bactericidal neutrophils and also to stimulate local IgA antibody formation (30). We noted that vaccination with H. pylori antigens together with either dmLT or CT as an adjuvant was associated with enhanced inflammation in the stomach (postimmunization gastritis) after challenge with live bacteria.…”
Section: ⌬Ctmentioning
confidence: 89%
“…[27][28][29] Several CD4 C T cell subsets have been implicated in germinal center (GC)-driven IgA responses including T-regulatory cells (Treg), 30 T-follicular helper cells (T FH ) 31 and Th17 cells. 32,33 It is likely that the generation of IgA C PC depends on the nature of the Ag and the location of where B cells are primed. Moreover, the precise combination of different leukocyte and mesenchymal cell types might influence the generation of IgA C PC.…”
mentioning
confidence: 99%
“…Similar to the previous paper by Dreesen et al, they showed that mice lacking IL-17RA were also defective in the control of G. muris infections and bone marrow chimeras indicated that the receptor was required on hematopoietic cells to mediate an effective antiparasitic effect. Additional comparisons of wild-type and IL-17A-deficient animals found that mice lacking IL-17A had significantly reduced fecal IgA levels both before and after infection, consistent with a role for IL-17 in inducing expression of the poly-Ig receptor that transports IgA from the serum into the intestinal lumen (15). IL-17A-deficient mice also had lower levels of mRNA encoding ␤-defensin-1, and IL-17RA-deficient mice had lower levels of mRNAs for resistin-like molecule ␤ (RELM-␤), serum amyloid A1 (Saa1), and serum amyloid A2 (Saa2), all proteins with potential antimicrobial and immunoregulatory functions (16)(17)(18)(19)(20).…”
Section: Cd197mentioning
confidence: 94%